Analysis of Fallacies in Croatian Parliamentary Debate - Kišiček, Gabrijela; Stanković, Davor (2011)
This research was aimed at analyzing the fallacies in argumentation of Croatian politicians. 20 sessions of Croatian National Parliament were used as a research material. The aim of the research was to find out whether there are differences in fallacies between left-wing and right-wing political parties as well as whether there are differences between the party in power and the opposition. The hypothesis that left-wing politicians would use argumentum ad misericordiam and the fallacy of neglected alternatives more often than left-wing politicians who would be more likely to use argumentum ad baculum, argumentum ad personam and appeal to authority has been confirmed by the analysis. The analysis has shown that some of the fallacies are common to all politicians ; one can say that they are universal in political speaking. Such fallacies are argumentum ad populum, argumentum ab utile, exemplum in contrarium, ex concessis, etc.
Projekt MZOS
ENG